Phytochemical Analysis, Antioxidant, and Wound Healing Activity of Pluchea indica L. (Less) Branch Extract Nanoparticles - Rattanakorn Chiangnoon; Weerasak Samee; Pimpon Uttayarat; Wullapa Jittachai; Warintorn Ruksiriwanich; Sarana Rose Sommano; Sirivan Athikomkulchai; Chuda Chittasupho (Molecules, 2022)
Proliferation and migration of keratinocytes and fibroblasts play an important role in cutaneous wound healing, while oral mucosal squamous cell proliferation and migration are crucial for oral wound healing. In this study, the phytochemical profile of Pluchea indica branch ethanolic extract was characterized. The bioactive compound of Pluchea indica branch ethanolic extract was identified and analyzed by the validated HPLC method. The nanoparticles of P. indica branch extract were formulated by solvent displacement method to increase the solubility and the colloidal stability of the extract. The stability of the nanoparticles was investigated by using the dynamic light scattering technique. Effects of P. indica crude extract and nanoparticles on cell viability, proliferation and migration of primary epidermal keratinocytes, human dermal fibroblasts, and oral mucosal keratinocyte cells were investigated by MTT assay and scratch assay, respectively. The results showed that P. indica branch extract contained a high content of total phenolic and total flavonoids. The HPLC analysis revealed that the main compound in the extract was 4,5-O-dicaffeoylquinic acid. The cell viability of the extract and nanoparticles decreased when cells were exposed to a high concentration of extract and nanoparticles. These results demonstrate that P. indica branch extract and extract nanoparticles at specific concentrations possess in vitro wound healing activity and they may be possibly used to treat different types of wounds including dermal and oral mucosal wounds.